2013
DOI: 10.1167/iovs.13-12544
|View full text |Cite
|
Sign up to set email alerts
|

The Rat With Oxygen-Induced Retinopathy Is Myopic With Low Retinal Dopamine

Abstract: The OIR rat is the first known animal model of myopia in which the eye is smaller than normal. Dopamine may modulate, or fail to modulate, neural activity in the OIR eye, and thus contribute to this peculiar myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 87 publications
5
21
0
4
Order By: Relevance
“…Thus, the control of eye growth is almost entirely a local phenomenon (Smith, 2011; Smith et al, 2013; Wallman et al, 1987; Wildsoet and Schmid, 2000). Our studies of refractive development in a rat model of ROP elegantly recapitulate our human findings of delayed growth, including of the anterior segment (Chui et al, 2012a; Zhang et al, 2013). If the neural retina controls eye growth, the abnormally avascular peripheral ROP retina may, therefore, underpin some of the abnormalities in the ROP eye, especially of the posterior segment.…”
Section: Eye Growth and Refractive Developmentsupporting
confidence: 76%
See 2 more Smart Citations
“…Thus, the control of eye growth is almost entirely a local phenomenon (Smith, 2011; Smith et al, 2013; Wallman et al, 1987; Wildsoet and Schmid, 2000). Our studies of refractive development in a rat model of ROP elegantly recapitulate our human findings of delayed growth, including of the anterior segment (Chui et al, 2012a; Zhang et al, 2013). If the neural retina controls eye growth, the abnormally avascular peripheral ROP retina may, therefore, underpin some of the abnormalities in the ROP eye, especially of the posterior segment.…”
Section: Eye Growth and Refractive Developmentsupporting
confidence: 76%
“…In any event, the short-eyed myopia found in the ROP rat offer insights about ocular development that cannot be obtained using traditional models of induced ametropia. For example, we have found that dopamine levels are low in ROP eyes, despite their being short (Zhang et al, 2013) and note the long-recognized role of dopamine as a “stop-signal” for eye growth (Iuvone et al, 1991). …”
Section: Eye Growth and Refractive Developmentsupporting
confidence: 52%
See 1 more Smart Citation
“…Retinal function was assessed by electroretinography (ERG) as previously described 27 in P30 untreated WT mice and…”
Section: Ergmentioning
confidence: 99%
“…на крысиной модели и Spix с соавт. на мышиной модели РН выявили снижение содержания ДА и его метаболита (ДОФУК) в сетчатке животных с РН [7,8]. Авторам удалось доказать, что на их моделях дефицит ДА L-ДОФА.…”
unclassified